FROM SILICON VALLEY TO TASHKENT: LESSONS FROM THE UNITED STATES’ TRIPLE HELIX EXPERIENCE FOR UZBEKISTAN’S INNOVATION ECOSYSTEM - Toshpulotov Shavkat Negmatullo ugli,; Khusanov Salokhiddin, (TADQIQOTLAR, 2026)
Abstract The Triple Helix Model conceptualises innovation as the product of dynamic interaction among universities, industry, and government. While the model has become a  dominant  framework  in  innovation  studies,  its  practical  application  in  transition economies remains underexplored. This article examines how the United States  — widely  regarded  as  the  archetype  of  an  advanced  Triple  Helix  system  —  has institutionalised university–industry–government collaboration across federal policy, corporate practice, and higher education. Drawing lessons from the US experience, the article  then  analyses  the  current  state  of  Uzbekistan’s  innovation  ecosystem, identifying the structural barriers that constrain Triple Helix development, including the legacy of Soviet-era institutional separation, weak university–industry linkages, limited research commercialisation, and human-capital outflow. The analysis is applied to a specific institutional case, the Tashkent Institute of Management and Economics (TIME),  demonstrating  how  the  framework  can  inform  institutional  strategy.  The article concludes with a set of government-level policy recommendations designed to accelerate  Uzbekistan’s  transition  toward  a  balanced,  interactive  Triple  Helix configuration.